ANALISIS STRATEGI PEMANFAATAN KAMUS HIWARI UNTUK MENGATASI PROBLEMATIKA PENGUASAAN ISTI'MAL KELAS X AGAMA MA JAMILURRAMAN - Fajar Amirudin; Habib Hassan As-Sajid; Ahmad Farid Alhaj; Yoga Saputra; Mubarok Mubarok (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze teachers’ strategies in utilizing Kamus Hiwari as a learning medium to address the problems of isti‘mal mastery (contextual vocabulary use) among tenth-grade Islamic students at MA Jamilurrahman. The research stems from the observation that students’ functional use of Arabic vocabulary remains low due to the dominance of rote-learning approaches in language instruction. A qualitative descriptive method with a field study design was employed, collecting data through participatory observation, in-depth interviews, and documentation of Arabic language teaching activities. The findings reveal that teachers implement three primary strategies in using Kamus Hiwari: meaning contextualization, collaborative learning, and integrative-evaluative strategies. These approaches effectively enhance students’ ability to understand and apply vocabulary within real communication contexts. However, several challenges were identified, including limited instructional time, passive dictionary use, and varying levels of vocabulary proficiency among students. To address these issues, teachers conducted contextual dictionary training, applied thematic vocabulary lists, and employed peer tutoring systems. The study concludes that the effectiveness of Kamus Hiwari depends largely on teachers’ creativity and pedagogical awareness in transforming it from a mere reference tool into a communicative learning medium that fosters contextual isti‘mal proficiency.